2020
DOI: 10.1016/j.tox.2020.152412
|View full text |Cite
|
Sign up to set email alerts
|

Sub-chronic exposure to Kalach 360 SL, Glyphosate-based Herbicide, induced bone rarefaction in female Wistar rats

Abstract: We investigated the effects of Kalach 360 SL (KL), Glyphosate (G)-based herbicide, on bone tissue in different groups of female Wistar rats. Group 1 (n=6) received a standard diet and served as a control, groups 2 and 3 (n=6 each) received 0.07ml (D1: 126 mg/Kg) and 0.175ml (D2: 315 mg/Kg) of KL dissolved in the water for 60 days. The plasma was used to examine the metabolic balance markers (calcium, phosphorus, phosphatase alkaline (PAL), and vitamin D (vit D) and hormonal status (oestrogen and thyroid hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
(58 reference statements)
2
10
0
Order By: Relevance
“…Glyphosate and GBHF Roundup Bioflow, and Kalach 360 SL decrease T4 and T3 hormone levels with an increase in TSH level (16)(17)(18) , and the result in the present study with the GBHF Roundup ® agrees with this. However, GBHF Roundup Transorb decreases the TSH level with no change in the T4 and T3 (19) .…”
Section: Changes In the Thyroid Hormones Levelssupporting
confidence: 89%
See 3 more Smart Citations
“…Glyphosate and GBHF Roundup Bioflow, and Kalach 360 SL decrease T4 and T3 hormone levels with an increase in TSH level (16)(17)(18) , and the result in the present study with the GBHF Roundup ® agrees with this. However, GBHF Roundup Transorb decreases the TSH level with no change in the T4 and T3 (19) .…”
Section: Changes In the Thyroid Hormones Levelssupporting
confidence: 89%
“…Less importance was been given to histopathological changes in the thyroid on exposure to GBHF. Few data is available on GBHF Kalach 360 SL (17) and the present study confirms and provides data on histopathological changes in the thyroid on exposure to GBHF Roundup ® .…”
Section: Histopathological Changes In the Thyroid Glandsupporting
confidence: 83%
See 2 more Smart Citations
“…Male and female offspring were sacrificed at PND73 (6 weeks) or PND125 (13 weeks) and an increase in serum TSH levels in males was observed after 6 weeks of treatment for glyphosate, and after 13 weeks for GBH. Hamdaoui et al (98) evaluated oral exposure to 126 mg/kg GBH during 60 days in female Wistar rats and investigated its action on bone tissue in correlation with the hormonal status of estrogen and thyroid gland. Histological and immunohistochemical analysis of the thyroid showed that after the exposure there was a relative increase in the appearance of follicles at rest with a consequent decrease in the number of active follicles, in addition to the appearance of macrophages, dilated follicles and flattened epithelium, with decreased volume of colloid.…”
Section: Glyphosate Toxicity In Hpt Axismentioning
confidence: 99%